Bugis philosophy in increasing multicultural awareness in the digital era - Resqi Pramana, Andi Dwi; Nurlaelah, Nurlaelah; yusmah, yusmah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Based on several research results, local wisdom values can help in raising awareness of cultural differences within a group, in this case at the Sidenreng Rappang Muhammadiyah University. The method used in this research was literature study and a random survey of students. The results of the research show that the values of sipakainge and sipakalebbi which are the principles of every student are able to make them aware of the meaning of multicultural differences that apply today